Comparison study on hysteretic energy dissipation and displacement components between cast‐in‐place and precast piers with high‐strength bars. (2nd November 2017) - Zhuo, Wei‐Ding; Liu, Zhao; Zhang, Jian‐Dong; Zhang, Wen‐Ming
Abstract : Precast piers incorporated with high‐strength bars (≥500 MPa) have great potential to accelerate bridge construction and enhance seismic performance. Four large‐scale pier column specimens using high‐strength bars by cast‐in‐place (CIP) and precast construction were experimentally studied. The distinctions of damage pattern between CIP and precast piers were characterized by plastic hinge and toed hinge, which expounded the smaller damage in precast piers. In contrast with CIP piers, the energy dissipation of precast pier was reduced by approximately 50–60% after pier yielding. An appropriate reinforcement ratio was essential for CIP piers to maintain enough displacement ductility and prevent premature fracture of energy dissipation bars. In terms of displacement components, the plastic term of precast pier was much smaller than that of CIP pier, and the gap opening‐induced displacement predominates after pier yielding. The toed hinge was elaborated to disclose the displacement mechanism in precast piers. The experimental findings in this paper can provide additional input for seismic design of precast piers with high‐strength bars.